Effect of denture cleansers on color stability and surface roughness of denture base acrylic resin - Hamidreza Rajati Haghi; Nafiseh Asadzadeh; Rasul Sahebalam; Mohammadreza Nakhaei; Jamal Zamani Amir (Wolters Kluwer Medknow Publications, 2015)
Background: Color stability of acrylic resin is one of the most important feature for denture wearers. Many patients use detergent solutions to remove denture stains. The purpose of this study was to evaluate color stability and surface roughness of two common acrylic resins in different detergent and tea solutions. Materials and Methods: 112 acrylic resin blocks of Meliodent and Acropars (each 56 blocks) were divided into seven groups of different treatment: 1% sodium hypochlorite for 10 min a day for 1 month (H10m), 1% sodium hypochlorite for 8 hours a day for 1 week (H&h), Correga tabs solution for 8 hours a day for 1 month (C&H), tea bag for 2 hours a day for 1 month (T2 h), tea bag for 2 hours a day then 10 min in 1% sodium hypochlorite for 1 month (T-H), tea bag for 2 hours then 8 hours in the Correga tab solution a day for 1 month (T-C), and finally distilled water for 1 month as a control group (con). After specimen's treatment, color (CIE Lab) and surface roughness (Ra, µm) of samples were measured. The results were analyzed by analysis of variance (ANOVA), followed by Tukey's HSD and Dunnett T3. Results: Group T2h exhibited a significant (P<0.05) color change and control specimens exhibited the lowest color change. Sodium hypochlorite caused a significant (P<0.05) color change in the Acropars group in comparison with the Meliodent group. In the Correga tab solution the difference was not significant (P=0.155). There was a significant (P<0.05) color change in the T-H treatment. The Acropars and Meliodent acrylic resin did not a show significant difference in surface roughness after different treatments. Conclusion: Sodium hypochlorite 1% for 10 minutes a day in a month is the recommended hygiene protocol. The color stability of acryl is brand-type dependent but surface roughness is not.